Social Intelligence in Islamic Education; Analysis of the Social Jurisprudence Ideas of KH. MA. Sahal Mahfudh - Prasetia, Senata Adi; Fahmi, Muhammad; Faizin, Moh. (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2023)
The article explores the development of social intelligence in Islamic education. In this period, Islamic education tended to be oriented only to cognitive and affective aspects but hardly to psychomotor ones. This shows that many students cannot interact with their environment. This article argues that the development of social intelligence in Islamic education under the guidance of KH. MA. Sahal Mahfudh focuses more on the aspects of social intelligence that are included in the idea of social fiqh. The findings suggest that the idea of social fiqh KH. MA. Sahal Mahfudh is the most essential foundation for the development of students' social intelligence. In this case, the development of social intelligence is displayed through social sensitivity, social insight, and social communication. Through education that focuses on social sensitivity, social knowledge and social communication, Kiai Sahal has created a strong foundation for developing aspects of social intelligence in the context of Islamic education in Indonesia. The concrete form of social intelligence development carried out by Kiai Sahal is reflected in the formulation of intellectual, social-community education, organizational education, sports and health education, and skills education. Applying the idea of social fiqh, Kiai Sahal in Islamic education should be a model and a new paradigm for developing social intelligence in learners.Abstrak: Artikel ini membahas bagaimana pengembangan kecerdasan sosial dalam pendidikan Islam dan relevansinya di era kontemporer perspektif KH. Sahal Mahfudh. Sebagai makhluk sosial, manusia tidak bisa hidup sendiri dan selalu memerlukan orang lain untuk berinteraksi. Atas dasar itu, pengembangan kecerdasan sosial dalam pendidikan Islam sangat dibutuhkan. Artikel ini berargumen bahwa pengembangan kecerdasan sosial dalam pendidikan Islam di bawah bimbingan KH. MA. Sahal Mahfudh lebih menitikberatkan pada aspek kecerdasan sosial yang tercakup dalam gagasan fikih sosial. Melalui penelitian kualitatif-eksploratif dan kepustakaan, serta dokumentasi dan pengayaan literatur serta analisis data menggunakan tiga aspek; kondensasi data, display data dan verifikasi data, hasil temuan menunjukkan bahwa gagasan fikih sosial KH. MA. Sahal Mahfudh menjadi basis utama bagi pengembangan kecerdasan sosial peserta didik. Dalam hal ini, perkembangan kecerdasan sosial ditampilkan melalui kepekaan sosial, wawasan sosial, dan komunikasi sosial. Melalui pendidikan yang terfokus pada sensitivitas sosial, pengetahuan sosial, dan komunikasi sosial, Kiai Sahal telah menciptakan landasan yang kuat guna pengembangan aspek kecerdasan sosial dalam konteks pendidikan Islam di Indonesia. Bentuk konkret pengembangan kecerdasan sosial yang dilakukan Kiai Sahal tercermin dalam rumusan pendidikan intelektual, pendidikan sosial kemasyarakatan, pendidikan organisasi, pendidikan olahraga dan kesehatan, serta pendidikan keterampilan. Penerapan pemikiran fikih sosial Kiai Sahal dalam pendidikan Islam hendaknya menjadi model dan paradigma baru dalam mengembangkan kecerdasan sosial pada peserta didik pada pendidikan Islam Indonesia kontemporer.